2020
DOI: 10.1186/s12879-020-05547-w
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of SCCmec elements and spa types in South African Staphylococcus aureus mecA-positive blood culture isolates

Abstract: Background The prevalence of Staphylococcus aureus varies depending on the healthcare facility, region and country. To understand its genetic diversity, transmission, dissemination, epidemiology and evolution in a particular geographical location, it is important to understand the similarities and variations in the population being studied. This can be achieved by using various molecular characterisation techniques. This study aimed to provide detailed molecular characterisation of South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(78 reference statements)
3
8
0
Order By: Relevance
“…The twenty spa types observed among the human in our study agrees with other reports elsewhere showing presence of multiple spa types among the MRSA isolates [25], [27]. However, differences has been observed in the spa types where we observed presence of; t1081, t701, t034, t041, t044, t037, t4677, t127, t1451, t9377, t032, t121, t922, t019, t108, t002, t030, t018, t040 and t012 in our region, while Vanessa et al reported t008, t020, t022, t104, t179, t718, t747, t910, t932, t1094, t2357, t5624, t10683 and t14933 in Portugal [24].This suggests diverse genetic backgrounds and multiple routes of their acquisition and spread.…”
Section: Discussionsupporting
confidence: 92%
“…The twenty spa types observed among the human in our study agrees with other reports elsewhere showing presence of multiple spa types among the MRSA isolates [25], [27]. However, differences has been observed in the spa types where we observed presence of; t1081, t701, t034, t041, t044, t037, t4677, t127, t1451, t9377, t032, t121, t922, t019, t108, t002, t030, t018, t040 and t012 in our region, while Vanessa et al reported t008, t020, t022, t104, t179, t718, t747, t910, t932, t1094, t2357, t5624, t10683 and t14933 in Portugal [24].This suggests diverse genetic backgrounds and multiple routes of their acquisition and spread.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, out of 61 MRSA strains, SCCmecI and SCCmec V, SCCmecII , SCCmecIII, and SCCmecIV genes were detected in 16.3, 22.9, 36.3, and 21.3% of isolates. This finding was also reported by some researchers from South Africa [ 16 ], Saudi Arabia [ 17 ], and Venezuela [ 18 ]. Surprisingly, none of the MSSA strains carried the VF genes.…”
Section: Discussionsupporting
confidence: 87%
“…ST5-VII [5C1] was recovered from a patient in the nephrology ward in Algeria ( Djoudi et al, 2014 ). Other reports include ST5-III/V/non-typeable (NT) in South Africa ( Abdulgader et al, 2020 ; Singh-Moodley et al, 2020 ). The related genotypes such as t6065-ST5/ST2629-V [5C2] in Angola ( Conceição et al, 2015a , b ), t6065-ST69-V [5C2] in Libya ( Khemiri et al, 2017 ), and t002-ST105-II [2A] in São Tomé and Príncipe ( Conceição et al, 2015b ) were also noted.…”
Section: Resultsmentioning
confidence: 99%